1995
DOI: 10.1111/j.1600-0897.1995.tb00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Perforin Expressing Lymphocytes Within the First Trimester Decidua of Human Pregnancy

Abstract: P expressing DL are prevalently nonclassical NK cells (CD16-) with low cytolytic activity but fully equipped with potent cytolytic machinery (Pbright+). There are no classical cytotoxic lymphocytes (CTL) (CD3+ CD8+ P+) in the decidua, and all CD8+ P+ cells are CD3- CD56+. The number of P+ cells is even higher in DP in the vicinity of noninvasive trophoblast, than in DB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…Their role in normal pregnancy is, however, still controversial. CD16-negative, perforinpositive, but non-cytotoxic NK cells have been reported in first trimester human decidua [29]. Thus, the relative proportion of decidual NK cells is increased in normal pregnancy compared with the non-pregnant uterus.…”
Section: Reduced Nk Cell Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…Their role in normal pregnancy is, however, still controversial. CD16-negative, perforinpositive, but non-cytotoxic NK cells have been reported in first trimester human decidua [29]. Thus, the relative proportion of decidual NK cells is increased in normal pregnancy compared with the non-pregnant uterus.…”
Section: Reduced Nk Cell Activitymentioning
confidence: 96%
“…Hence, there is a potential for the initiation of a vicious circle. The final mechanism by which activated NK cells kill their target cells is exocytosis of perforin and serine esterase -containing granules in the contact area between effector (LAK) and target (trophoblast) cells [29,48].…”
Section: Increased Nk Cell Activity and Lymphokine Activated Killer Cmentioning
confidence: 99%
“…Under certain conditions, e.g., when exposed to hCMV-infected autologous decidual cells [58] or during spontaneous abortion in mice [59], they degranulate, but during normal pregnancy these cells are not cytotoxic despite the abundant presence of cytotoxic molecules in their cytoplasmic granules [60,61].…”
Section: Pibf Regulates Nk Activity During Pregnancymentioning
confidence: 99%
“…It has been reported that the lack of perforin expression in the uNK cells does not measurably restrain successful pregnancy and reproduction, i.e., perforin-deficient mothers were able to give birth to the same number of syngeneic or semi-allogeneic litters of similar sizes as control mice [11,16]. Our result also showed that although the cell population of uNK cells in P -/-mice was tended to be higher than B6 mice at Day 12, there is not significant difference between these 2 groups.…”
mentioning
confidence: 99%